Case of the month: Dislodged tracheo-oesophageal valve: importance of rapid replacement or stenting. Issue 4 (20th March 2006) - Hathurusinghe, H; Uppal, H; Shortridge, R; Read, C
Abstract : Dislodgement of a tracheo-oesophageal prosthesis needs prompt action to ensure patency and prevent aspiration in patients with total laryngectomy. Failure to do so may lead to an unnecessary repeat tracheo-oesophageal puncture. This case report is about a patient who needed a repeat procedure under general anaesthetic. It highlights the need for emergency physicians to be aware of this not uncommon event in a patient with a laryngectomy and to refer them immediately for ENT review.